Pedestrian network repair with spatial optimization models and geocrowdsourced data - Qin, Han; Curtin, Kevin M.; Rice, Matthew T. (GeoJournal, 2018)
Pedestrian infrastructure is an essential part of the urban fabric. Typically, it is carefully planned and maintained by governments and local experts, who recognize the benefits to health, wellbeing, and even economics associated with a walkable environment. Pedestrian walkway characteristics, including running slope, cross slope, curb cuts, cross walks, sidewalk widths, and signalization are a part of the comprehensive design elements used by most municipalities. However, barriers or obstacles, including temporary obstructions, construction detours, and surface irregularities make this infrastructure difficult for individuals with a mobility impairment or vision impairment to use. Crowdsourcing can assist these individuals by providing information about transient and permanent navigation obstacles, through an accessibility mapping system. Accessibility mapping systems, several examples of which are discussed in this paper, provide routing functions to make navigation easier for individuals with a mobility impairment or vision impairment. A geocrowdsourced accessibility system can also identify deficiencies in a pedestrian network dynamically, and can provision routing and obstacle avoidance functions in real-time, with data about transient events provided by the public. This paper is based upon previous geocrowdsourced data quality studies, and presents a modeling methodology to identify high-value routing corridors in a dynamic geocrowdsourced accessibility system. The corridor measurement can help civic employees from city public works and transportation departments prioritize maintenance of a pedestrian infrastructure, including the rectification of obstacles identified through crowdsourcing. In this paper, we augment geocrowdsourcing data quality metrics with input from subject matter experts trained in orientation and mobility services, and discuss the accessibility elements that could directly influence the usability of the pedestrian infrastructure. We also present a cost optimization model to measure the value of a pedestrian network segment. Lastly, this paper analyzes how the value of a network segment in a geocrowdsourced accessibility system changes with network conditions and how this relates to prioritization of maintenance tasks through optimization criteria.